A dynamic peripheral immune landscape during human pregnancy - Xiuxing Liu; Lei Zhu; Zhaohao Huang; Zhaohuai Li; Runping Duan; He Li; Lihui Xie; Xiaozhen Chen; Wen Ding; Binyao Chen; Yuehan Gao; Juan Su; et al. (Fundamental Research)
Extensive immune adaptations occur during pregnancy to ensure successful delivery. However, these changes can increase the risk of disease in the mother. Here, we conducted single-cell RNA sequencing on peripheral blood mononuclear cells from pregnant women at different stages of pregnancy to elucidate the dynamic transcriptional changes in the maternal immune system. Gradual reduced cytotoxicity phenotype in highly variable cytotoxic T and natural killer cell types were observed during pregnancy. Reduced T- and B-cell response-related MHC-II and CD40 signaling as well as enhanced protolerance inducible costimulator and activin signaling may underlie the pregnancy-related weakening of adaptive immunity. Conversely, pro-inflammatory genes and pathways were upregulated in monocytes, possibly to compensate for the reduced T-cell response. Moreover, the transition from adaptive immune reduction to activation in late pregnancy in dendritic cells and CD4+ T cells was also detected. Notably, we proposed a novel view of the pro-aging effect of pregnancy from the perspective of immunity, and this effect may be restored postpartum. This work expands our knowledge of pregnancy immunity and may provide insights into the altered disease risks during pregnancy.